Analysis on vibration monitoring at mrt infrastructure construction site - Tumiran, Mohamad Taufik (2015)
The study focused on monitoring the level of Peak Vertical Vibration Velocity, mmls at one axis, and was conducted at the Bukit Bintang MRT Station and Kajang MRT construction. Polytec Laser Doppler Vibrometer (LDV) was used to measure the level of vibration during construction operation. The collaboration with the government local authority such as Land Public Transportation Commission (SPAD) and the project owner MRT Corp itself has helped the studies conducted successfully. Data obtained were analyzed on different sources of vibration which is from ambient, normal excavation, deep excavation and boring works and all data was taken within 25m away from the sources of the vibration. The result from the field measurement by different type of machines have been compared Eurocode 3 and DOE Malaysia. According to recommended limit for structural damage based on Eurocode 3, the safety distances for Bauer BG 28, Komatsu PC200, Liebherr HS 855 HD Litronic, and Sumitomo SH120-3 with TB220 attachment in residential area are 177 m, 15 m, 7 m, and 19.7 m away from the source or receiver. While in commercial land use, it is predicted to be 25 m, 5.3 my 1 m, and 3.4 m respectively. However, DOE guidelines have lower structural damage criterion if compared with Eurocode 3 whereas the recommended limits for damage risk in buildings from steady state vibration only gave the range of frequency and the safety parameters. For human response and annoyance criterion, it seems the use of Bauer BG 28 generates the highest vibration which could discomfort the environment. Based on DOE guideline, the limit for residential area was between 1.2 mm/s to 2.2 mmls, while for commercial use was between 2.2 mmls to 2.9 mm/s respectively. The predicted safety distance from the finding was between 342 m to 2.1 km away from the receiver. While the assessment based on Eurocode 3 found that the use of Bauer BG 28 must be at least separated at 1.2 km away for the construction period less than 6 days.